Rock art provides new evidence on the biogeography of kudu (Tragelaphus imberbis), wild dromedary, aurochs (Bos primigenius) and African wild ass (Equus africanus) in the early and middle Holocene of north‐western Arabia. (14th January 2018) - Guagnin, Maria; Shipton, Ceri; el‐Dossary, Sarah; al‐Rashid, Moudhy; Moussa, Farès; Stewart, Mathew; Ott, Florian; Alsharekh, Abdullah; Petraglia, Michael D.
Abstract: Aim: Our knowledge of the prehistoric distribution of animal species is so far largely dependent on the location of excavated archaeological and palaeontological sites. In the absence of excavated faunal remains, many species that were present in the Levant and North Africa have been assumed to have been absent on the Arabian Peninsula. Here, we explore representations of four species that were identifiable in the rock art, but had not previously been reported in north‐western Arabia. Location: Jubbah and Shuwaymis UNESCO world heritage rock art sites in Ha'il province, north‐western Saudi Arabia. Methods: In total, the rock art panels surveyed and recorded in Jubbah and Shuwaymis contain 6, 618 individual animal depictions. Species were identified based on diagnostic features of the anatomy. The resulting dataset was then compared to the faunal spectrum reported in the (archaeo)zoological literature. Results: The rock art dataset provides evidence that the distributions of lesser kudu ( Tragelaphus imberbis ), wild camel and African wild ass ( Equus africanus ) extended into the north‐west of Arabia and that the engravers may have had knowledge of aurochs ( Bos primigenius ). Main conclusions: The presence of previously undocumented mammal species in Arabia provides new information regarding their distribution, as well as the types of habitat and vegetation that were available in prehistoric landscapes. Moreover, the presence of kudu on the Arabian Peninsula indicates that the identification of palaeo‐distributions based exclusively on faunal remains may miss key species in the Afro‐Eurasian faunal exchange.